Development of Fibre Bragg Grating based Inclinometer designs - Xu, Zunwei (2017)
This report discusses about a Land Transport Authority (LTA) funded project to design This report discusses about a Land Transport Authority (LTA) funded project to design This report discusses about a Land Transport Authority (LTA) funded project to design This report discusses about a Land Transport Authority (LTA) funded project to design This report discusses about a Land Transport Authority (LTA) funded project to design This report discusses about a Land Transport Authority (LTA) funded project to design This report discusses about a Land Transport Authority (LTA) funded project to design This report discusses about a Land Transport Authority (LTA) funded project to design This report discusses about a Land Transport Authority (LTA) funded project to design This report discusses about a Land Transport Authority (LTA) funded project to design This report discusses about a Land Transport Authority (LTA) funded project to design This report discusses about a Land Transport Authority (LTA) funded project to design This report discusses about a Land Transport Authority (LTA) funded project to design This report discusses about a Land Transport Authority (LTA) funded project to design This report discusses about a Land Transport Authority (LTA) funded project to design This report discusses about a Land Transport Authority (LTA) funded project to design This report discusses about a Land Transport Authority (LTA) funded project to design This report discusses about a Land Transport Authority (LTA) funded project to design This report discusses about a Land Transport Authority (LTA) funded project to design This report discusses about a Land Transport Authority (LTA) funded project to design This report discusses about a Land Transport Authority (LTA) funded project to design This report discusses about a Land Transport Authority (LTA) funded project to design This report discusses about a Land Transport Authority (LTA) funded project to design This report discusses about a Land Transport Authority (LTA) funded project to design This report discusses about a Land Transport Authority (LTA) funded project to design This report discusses about a Land Transport Authority (LTA) funded project to design This report discusses about a Land Transport Authority (LTA) funded project to design This report discusses about a Land Transport Authority (LTA) funded project to design This report discusses about a Land Transport Authority (LTA) funded project to design This report discusses about a Land Transport Authority (LTA) funded project to design This report discusses about a Land Transport Authority (LTA) funded project to design This report discusses about a Land Transport Authority (LTA) funded project to design This report discusses about a Land Transport Authority (LTA) funded project to design This report discusses about a Land Transport Authority (LTA) funded project to design This report discusses about a Land Transport Authority (LTA) funded project to design This report discusses about a Land Transport Authority (LTA) funded project to design new type of inclinometer using Fibre Bragg Grating (FBG) sensors instead the new type of inclinometer using Fibre Bragg Grating (FBG) sensors instead the new type of inclinometer using Fibre Bragg Grating (FBG) sensors instead the new type of inclinometer using Fibre Bragg Grating (FBG) sensors instead the new type of inclinometer using Fibre Bragg Grating (FBG) sensors instead the new type of inclinometer using Fibre Bragg Grating (FBG) sensors instead the new type of inclinometer using Fibre Bragg Grating (FBG) sensors instead the new type of inclinometer using Fibre Bragg Grating (FBG) sensors instead the new type of inclinometer using Fibre Bragg Grating (FBG) sensors instead the new type of inclinometer using Fibre Bragg Grating (FBG) sensors instead the new type of inclinometer using Fibre Bragg Grating (FBG) sensors instead the new type of inclinometer using Fibre Bragg Grating (FBG) sensors instead the new type of inclinometer using Fibre Bragg Grating (FBG) sensors instead the new type of inclinometer using Fibre Bragg Grating (FBG) sensors instead the new type of inclinometer using Fibre Bragg Grating (FBG) sensors instead the new type of inclinometer using Fibre Bragg Grating (FBG) sensors instead the new type of inclinometer using Fibre Bragg Grating (FBG) sensors instead the new type of inclinometer using Fibre Bragg Grating (FBG) sensors instead the new type of inclinometer using Fibre Bragg Grating (FBG) sensors instead the new type of inclinometer using Fibre Bragg Grating (FBG) sensors instead the new type of inclinometer using Fibre Bragg Grating (FBG) sensors instead the new type of inclinometer using Fibre Bragg Grating (FBG) sensors instead the new type of inclinometer using Fibre Bragg Grating (FBG) sensors instead the new type of inclinometer using Fibre Bragg Grating (FBG) sensors instead the new type of inclinometer using Fibre Bragg Grating (FBG) sensors instead the new type of inclinometer using Fibre Bragg Grating (FBG) sensors instead the new type of inclinometer using Fibre Bragg Grating (FBG) sensors instead the new type of inclinometer using Fibre Bragg Grating (FBG) sensors instead the new type of inclinometer using Fibre Bragg Grating (FBG) sensors instead the new type of inclinometer using Fibre Bragg Grating (FBG) sensors instead the new type of inclinometer using Fibre Bragg Grating (FBG) sensors instead the new type of inclinometer using Fibre Bragg Grating (FBG) sensors instead the new type of inclinometer using Fibre Bragg Grating (FBG) sensors instead the new type of inclinometer using Fibre Bragg Grating (FBG) sensors instead the new type of inclinometer using Fibre Bragg Grating (FBG) sensors instead the new type of inclinometer using Fibre Bragg Grating (FBG) sensors instead the new type of inclinometer using Fibre Bragg Grating (FBG) sensors instead the new type of inclinometer using Fibre Bragg Grating (FBG) sensors instead the new type of inclinometer using Fibre Bragg Grating (FBG) sensors instead the new type of inclinometer using Fibre Bragg Grating (FBG) sensors instead the conventional inclinometers in achieving more reliable reconventional inclinometers in achieving more reliable re conventional inclinometers in achieving more reliable re conventional inclinometers in achieving more reliable re conventional inclinometers in achieving more reliable re conventional inclinometers in achieving more reliable re conventional inclinometers in achieving more reliable reconventional inclinometers in achieving more reliable re conventional inclinometers in achieving more reliable re conventional inclinometers in achieving more reliable re conventional inclinometers in achieving more reliable reconventional inclinometers in achieving more reliable reconventional inclinometers in achieving more reliable re conventional inclinometers in achieving more reliable reconventional inclinometers in achieving more reliable reconventional inclinometers in achieving more reliable re conventional inclinometers in achieving more reliable reconventional inclinometers in achieving more reliable reconventional inclinometers in achieving more reliable reconventional inclinometers in achieving more reliable re conventional inclinometers in achieving more reliable reconventional inclinometers in achieving more reliable re conventional inclinometers in achieving more reliable reconventional inclinometers in achieving more reliable result and alternative method to sult and alternative method to sult and alternative method to sult and alternative method to sult and alternative method to sult and alternative method to sult and alternative method to sult and alternative method to sult and alternative method to sult and alternative method to sult and alternative method to sult and alternative method to sult and alternative method to sult and alternative method to sult and alternative method to capture and manage data collected. capture and manage data collected. capture and manage data collected. capture and manage data collected. capture and manage data collected. capture and manage data collected. capture and manage data collected. capture and manage data collected. capture and manage data collected. capture and manage data collected. capture and manage data collected. capture and manage data collected. capture and manage data collected. capture and manage data collected. capture and manage data collected. capture and manage data collected. capture and manage data collected. capture and manage data collected. capture and manage data collected. capture and manage data collected. This report first describe This report first describe This report first describe This report first describe This report first describe This report first describe This report first describe This report first describe This report first describe s about the fundaments of about the fundaments of about the fundaments of about the fundaments of about the fundaments of about the fundaments of about the fundaments of how conventional how conventional how conventional how conventional how conventional how conventional inclinometers are used to measure underground movement, how Fibre inclinometers are used to measure underground movement, how Fibre inclinometers are used to measure underground movement, how Fibre inclinometers are used to measure underground movement, how Fibre inclinometers are used to measure underground movement, how Fibre inclinometers are used to measure underground movement, how Fibre inclinometers are used to measure underground movement, how Fibre inclinometers are used to measure underground movement, how Fibre inclinometers are used to measure underground movement, how Fibre inclinometers are used to measure underground movement, how Fibre inclinometers are used to measure underground movement, how Fibre inclinometers are used to measure underground movement, how Fibre inclinometers are used to measure underground movement, how Fibre inclinometers are used to measure underground movement, how Fibre inclinometers are used to measure underground movement, how Fibre inclinometers are used to measure underground movement, how Fibre inclinometers are used to measure underground movement, how Fibre inclinometers are used to measure underground movement, how Fibre inclinometers are used to measure underground movement, how Fibre inclinometers are used to measure underground movement, how Fibre inclinometers are used to measure underground movement, how Fibre Bragg Grating (FBG) sensorsBragg Grating (FBG) sensors Bragg Grating (FBG) sensors Bragg Grating (FBG) sensorsBragg Grating (FBG) sensors Bragg Grating (FBG) sensorsBragg Grating (FBG) sensors Bragg Grating (FBG) sensorsBragg Grating (FBG) sensorsBragg Grating (FBG) sensorsBragg Grating (FBG) sensorsBragg Grating (FBG) sensorsBragg Grating (FBG) sensorsBragg Grating (FBG) sensors Bragg Grating (FBG) sensorsBragg Grating (FBG) sensors Bragg Grating (FBG) sensors can be incorporated into inclinometercan be incorporated into inclinometercan be incorporated into inclinometer can be incorporated into inclinometer can be incorporated into inclinometercan be incorporated into inclinometer can be incorporated into inclinometercan be incorporated into inclinometer can be incorporated into inclinometercan be incorporated into inclinometer can be incorporated into inclinometer can be incorporated into inclinometer can be incorporated into inclinometer can be incorporated into inclinometer can be incorporated into inclinometercan be incorporated into inclinometer . By evaluating the By evaluating the By evaluating the By evaluating the By evaluating the By evaluating the By evaluating the By evaluating the By evaluating the By evaluating the strength and limitation of conventional inclinometers other FBG inclinometer designs, strength and limitation of conventional inclinometers other FBG inclinometer designs, strength and limitation of conventional inclinometers other FBG inclinometer designs, strength and limitation of conventional inclinometers other FBG inclinometer designs, strength and limitation of conventional inclinometers other FBG inclinometer designs, strength and limitation of conventional inclinometers other FBG inclinometer designs, strength and limitation of conventional inclinometers other FBG inclinometer designs, strength and limitation of conventional inclinometers other FBG inclinometer designs, strength and limitation of conventional inclinometers other FBG inclinometer designs, strength and limitation of conventional inclinometers other FBG inclinometer designs, strength and limitation of conventional inclinometers other FBG inclinometer designs, strength and limitation of conventional inclinometers other FBG inclinometer designs, strength and limitation of conventional inclinometers other FBG inclinometer designs, strength and limitation of conventional inclinometers other FBG inclinometer designs, strength and limitation of conventional inclinometers other FBG inclinometer designs, strength and limitation of conventional inclinometers other FBG inclinometer designs, strength and limitation of conventional inclinometers other FBG inclinometer designs, strength and limitation of conventional inclinometers other FBG inclinometer designs, strength and limitation of conventional inclinometers other FBG inclinometer designs, strength and limitation of conventional inclinometers other FBG inclinometer designs, strength and limitation of conventional inclinometers other FBG inclinometer designs, strength and limitation of conventional inclinometers other FBG inclinometer designs, strength and limitation of conventional inclinometers other FBG inclinometer designs, strength and limitation of conventional inclinometers other FBG inclinometer designs, strength and limitation of conventional inclinometers other FBG inclinometer designs, strength and limitation of conventional inclinometers other FBG inclinometer designs, strength and limitation of conventional inclinometers other FBG inclinometer designs, strength and limitation of conventional inclinometers other FBG inclinometer designs, strength and limitation of conventional inclinometers other FBG inclinometer designs, strength and limitation of conventional inclinometers other FBG inclinometer designs, strength and limitation of conventional inclinometers other FBG inclinometer designs, strength and limitation of conventional inclinometers other FBG inclinometer designs, strength and limitation of conventional inclinometers other FBG inclinometer designs, strength and limitation of conventional inclinometers other FBG inclinometer designs, strength and limitation of conventional inclinometers other FBG inclinometer designs, two new designs are proposed to suit the requirement of LTA for a FBG inclinometer. two new designs are proposed to suit the requirement of LTA for a FBG inclinometer. two new designs are proposed to suit the requirement of LTA for a FBG inclinometer. two new designs are proposed to suit the requirement of LTA for a FBG inclinometer.two new designs are proposed to suit the requirement of LTA for a FBG inclinometer.two new designs are proposed to suit the requirement of LTA for a FBG inclinometer. two new designs are proposed to suit the requirement of LTA for a FBG inclinometer. two new designs are proposed to suit the requirement of LTA for a FBG inclinometer.two new designs are proposed to suit the requirement of LTA for a FBG inclinometer.two new designs are proposed to suit the requirement of LTA for a FBG inclinometer.two new designs are proposed to suit the requirement of LTA for a FBG inclinometer.two new designs are proposed to suit the requirement of LTA for a FBG inclinometer.two new designs are proposed to suit the requirement of LTA for a FBG inclinometer. two new designs are proposed to suit the requirement of LTA for a FBG inclinometer. two new designs are proposed to suit the requirement of LTA for a FBG inclinometer. two new designs are proposed to suit the requirement of LTA for a FBG inclinometer. two new designs are proposed to suit the requirement of LTA for a FBG inclinometer. two new designs are proposed to suit the requirement of LTA for a FBG inclinometer.two new designs are proposed to suit the requirement of LTA for a FBG inclinometer. two new designs are proposed to suit the requirement of LTA for a FBG inclinometer.two new designs are proposed to suit the requirement of LTA for a FBG inclinometer.two new designs are proposed to suit the requirement of LTA for a FBG inclinometer. two new designs are proposed to suit the requirement of LTA for a FBG inclinometer. two new designs are proposed to suit the requirement of LTA for a FBG inclinometer. two new designs are proposed to suit the requirement of LTA for a FBG inclinometer. two new designs are proposed to suit the requirement of LTA for a FBG inclinometer.two new designs are proposed to suit the requirement of LTA for a FBG inclinometer.two new designs are proposed to suit the requirement of LTA for a FBG inclinometer.two new designs are proposed to suit the requirement of LTA for a FBG inclinometer.two new designs are proposed to suit the requirement of LTA for a FBG inclinometer. two new designs are proposed to suit the requirement of LTA for a FBG inclinometer.two new designs are proposed to suit the requirement of LTA for a FBG inclinometer.two new designs are proposed to suit the requirement of LTA for a FBG inclinometer.two new designs are proposed to suit the requirement of LTA for a FBG inclinometer.two new designs are proposed to suit the requirement of LTA for a FBG inclinometer.two new designs are proposed to suit the requirement of LTA for a FBG inclinometer. two new designs are proposed to suit the requirement of LTA for a FBG inclinometer. two new designs are proposed to suit the requirement of LTA for a FBG inclinometer.two new designs are proposed to suit the requirement of LTA for a FBG inclinometer. two new designs are proposed to suit the requirement of LTA for a FBG inclinometer. two new designs are proposed to suit the requirement of LTA for a FBG inclinometer.two new designs are proposed to suit the requirement of LTA for a FBG inclinometer. The The The report then explains report then explains report then explains report then explainsreport then explainsreport then explainsreport then explains about the theory and idea on how FBG based inclinometer works about the theory and idea on how FBG based inclinometer works about the theory and idea on how FBG based inclinometer works about the theory and idea on how FBG based inclinometer works about the theory and idea on how FBG based inclinometer works about the theory and idea on how FBG based inclinometer works about the theory and idea on how FBG based inclinometer works about the theory and idea on how FBG based inclinometer works about the theory and idea on how FBG based inclinometer works about the theory and idea on how FBG based inclinometer works about the theory and idea on how FBG based inclinometer works about the theory and idea on how FBG based inclinometer works about the theory and idea on how FBG based inclinometer works about the theory and idea on how FBG based inclinometer works about the theory and idea on how FBG based inclinometer works about the theory and idea on how FBG based inclinometer works about the theory and idea on how FBG based inclinometer works about the theory and idea on how FBG based inclinometer works about the theory and idea on how FBG based inclinometer works about the theory and idea on how FBG based inclinometer works about the theory and idea on how FBG based inclinometer works about the theory and idea on how FBG based inclinometer works about the theory and idea on how FBG based inclinometer works about the theory and idea on how FBG based inclinometer works about the theory and idea on how FBG based inclinometer works about the theory and idea on how FBG based inclinometer works about the theory and idea on how FBG based inclinometer works about the theory and idea on how FBG based inclinometer works about the theory and idea on how FBG based inclinometer works about the theory and idea on how FBG based inclinometer works about the theory and idea on how FBG based inclinometer works about the theory and idea on how FBG based inclinometer works about the theory and idea on how FBG based inclinometer works about the theory and idea on how FBG based inclinometer works discuss about some experimental data and results we have collected, discuss about some experimental data and results we have collected, discuss about some experimental data and results we have collected, discuss about some experimental data and results we have collected, discuss about some experimental data and results we have collected, discuss about some experimental data and results we have collected, discuss about some experimental data and results we have collected, discuss about some experimental data and results we have collected, discuss about some experimental data and results we have collected, discuss about some experimental data and results we have collected, discuss about some experimental data and results we have collected, discuss about some experimental data and results we have collected, discuss about some experimental data and results we have collected, discuss about some experimental data and results we have collected, discuss about some experimental data and results we have collected, discuss about some experimental data and results we have collected, discuss about some experimental data and results we have collected, discuss about some experimental data and results we have collected, discuss about some experimental data and results we have collected, discuss about some experimental data and results we have collected, discuss about some experimental data and results we have collected, discuss about some experimental data and results we have collected, discuss about some experimental data and results we have collected, discuss about some experimental data and results we have collected, discuss about some experimental data and results we have collected, discuss about some experimental data and results we have collected, discuss about some experimental data and results we have collected, discuss about some experimental data and results we have collected, with in with in -depth depth depth evaluation of the experiments and results, further implementations are suggested.evaluation of the experiments and results, further implementations are suggested. evaluation of the experiments and results, further implementations are suggested. evaluation of the experiments and results, further implementations are suggested. evaluation of the experiments and results, further implementations are suggested.evaluation of the experiments and results, further implementations are suggested. evaluation of the experiments and results, further implementations are suggested. evaluation of the experiments and results, further implementations are suggested. evaluation of the experiments and results, further implementations are suggested. evaluation of the experiments and results, further implementations are suggested. evaluation of the experiments and results, further implementations are suggested. evaluation of the experiments and results, further implementations are suggested. evaluation of the experiments and results, further implementations are suggested. evaluation of the experiments and results, further implementations are suggested. evaluation of the experiments and results, further implementations are suggested. evaluation of the experiments and results, further implementations are suggested.evaluation of the experiments and results, further implementations are suggested. evaluation of the experiments and results, further implementations are suggested. evaluation of the experiments and results, further implementations are suggested.evaluation of the experiments and results, further implementations are suggested.